2008
DOI: 10.1242/jeb.018028
|View full text |Cite
|
Sign up to set email alerts
|

Redundancy of olfactory sensory pathways for odor-aversion memory in the terrestrial slug Limax valentianus

Abstract: Terrestrial slugs Limax valentianus (Férussac 1822) (12-16 weeks post hatching) have been maintained in our laboratory at 19°C for at least nine generations as a closed colony. They have been fed only on a diet of humidified powder mixture consisting of 521·g rat chow (Oriental Yeast, Tokyo, Japan), 500·g wheat starch (Wako Pure Chemicals, Osaka, Japan) and 21·g vitamins (Oriental Yeast). Accepted 1 April 2008 SUMMARY Terrestrial slugs have the ability to learn and remember a food odor paired with an aversive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…We previously showed that the memory acquired with two pairs of tentacles can even be retrieved using either one of the superior or inferior tentacles, and that the memory can be acquired and retrieved using either one of the superior or inferior tentacles (Yamagishi et al, 2008). These findings do not contradict our present results, because the same pairs of superior or inferior tentacles were functional both during the acquisition and retrieval of the memory in that study (Yamagishi et al, 2008).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…We previously showed that the memory acquired with two pairs of tentacles can even be retrieved using either one of the superior or inferior tentacles, and that the memory can be acquired and retrieved using either one of the superior or inferior tentacles (Yamagishi et al, 2008). These findings do not contradict our present results, because the same pairs of superior or inferior tentacles were functional both during the acquisition and retrieval of the memory in that study (Yamagishi et al, 2008).…”
Section: Discussionsupporting
confidence: 78%
“…These findings do not contradict our present results, because the same pairs of superior or inferior tentacles were functional both during the acquisition and retrieval of the memory in that study (Yamagishi et al, 2008). Friedrich and Teyke (1998), using an anesthetic agent, reported that the terrestrial snail Helix is unable to retrieve an appetitive olfactory memory if a different side (right or left) of the superior and inferior tentacles is allowed to function during memory acquisition and retrieval.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In one group, the slugs were conditioned with carrot juice six days after amputation of the inferior tentacle. It has been demonstrated previously that the amputated tentacles do not regenerate in a recovery period as short as six days (Yamagishi et al, 2008). However, the superior tentacles, amputated 34 days before, showed regeneration to some extent at this time (R.M., unpublished observations).…”
Section: The Slugs Were Capable Of Learning Five Weeks After Amputatimentioning
confidence: 73%
“…The tentacle amputation of the slugs (12-13 weeks post hatching) was performed under anesthesia, as described previously (Yamagishi et al, 2008;Matsuo et al, 2010b -1 Hepes, pH 7.0) was injected into the body cavity to improve the recovery from anesthetization. After surgery, two to five (usually three) slugs were transferred to a plastic container and maintained with free access to the humidified powder mixture until the next procedure -that is, in vitro LFP recording or histological analysis.…”
Section: Surgerymentioning
confidence: 99%